2009
DOI: 10.1161/circulationaha.108.821082
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Sensitized Zebrafish Screen Identifies Multiple Genes, Including GINS3 , as Regulators of Myocardial Repolarization

Abstract: Background-Cardiac repolarization, the process by which cardiomyocytes return to their resting potential after each beat, is a highly regulated process that is critical for heart rhythm stability. Perturbations of cardiac repolarization increase the risk for life-threatening arrhythmias and sudden cardiac death. Although genetic studies of familial long-QT syndromes have uncovered several key genes in cardiac repolarization, the major heritable contribution to this trait remains unexplained. Identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 40 publications
4
119
0
Order By: Relevance
“…The wavefront fractionation might also represent intercalation of noncoupled epicardial cells into the myocardium with resultant conduction block and delayed subepicardial impulse propagation. In addition to the conduction findings, the prolongation of action potential duration and diminution of peak action potential upstroke velocities recapitulate the electrical phenotypes of less differentiated cardiomyocytes (Milan et al, 2009;Panakova et al, 2010). Such changes in action potential upstroke velocity probably represent an increased dependence of depolarization on calcium channel conductance and a reduced role for sodium channel conductance (Chopra et al, 2010;Milan et al, 2009;Panakova et al, 2010).…”
Section: Ultrastructural and Physiological De-differentiation In Sourmentioning
confidence: 55%
“…The wavefront fractionation might also represent intercalation of noncoupled epicardial cells into the myocardium with resultant conduction block and delayed subepicardial impulse propagation. In addition to the conduction findings, the prolongation of action potential duration and diminution of peak action potential upstroke velocities recapitulate the electrical phenotypes of less differentiated cardiomyocytes (Milan et al, 2009;Panakova et al, 2010). Such changes in action potential upstroke velocity probably represent an increased dependence of depolarization on calcium channel conductance and a reduced role for sodium channel conductance (Chopra et al, 2010;Milan et al, 2009;Panakova et al, 2010).…”
Section: Ultrastructural and Physiological De-differentiation In Sourmentioning
confidence: 55%
“…The genome-wide association scan approach to normal QT has also implicated common variants in cLQTS disease genes (SCN5A, KCNJ2, KCNQ1, and KCNH2), other genes thought to play a role in cardiac electrophysiology (e.g., phospholamban, a regulator of intracellular calcium), and entirely new loci. One of 776 these includes GINS3, which has also been implicated as a modulator of heart-rate response to dofetilide challenge in zebrafish (Milan et al, 2009).…”
Section: Common Variantsmentioning
confidence: 99%
“…Recent work in mice investigating congenital heart disease in individuals with DS exclude Chd5 from the minimal region that induces congenital heart disease upon duplication (Liu et al, 2011a). By contrast, a recent screen in zebrafish identified CHD5 as a regulator of myocardial repolarization (Milan et al, 2009), and subsequent work in the medaka fish demonstrated that CHD5-depleted hearts had general looping and chamber defects (Murata et al, 2009). Our results demonstrate for the first time a mechanism by which CHD5 functions during cardiac development via interaction with a cardiac transcription factor and demonstrate cardiac defects in CHD5-depleted embryos.…”
Section: Chd5 Has Distinct Dual Functions During Developmentmentioning
confidence: 99%
“…CHD5, initially identified in a screen for genes within a restricted region of chromosome 21 associated with heart disease in individuals with DS, was found to be expressed in fetal hearts and shown to localize predominately to the nuclei of cells of cardiac origin (Egeo et al, 1998). CHD5 was also identified in a drug-sensitized screen in zebrafish as a regulator of myocardial repolarization (Milan et al, 2009) and depletion of CHD5 in medaka fish has been reported to be associated with general cardiac defects of unknown etiology (Murata et al, 2009). In addition to these findings, CHD5 has also been reported to be localized to the membrane of the endoplasmic reticulum (ER), where it is proposed to function as a receptor to transport charged proteins across the ER membrane (Ando and Suzuki, 2005;Vilardi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%